Regenerative grazing For climate, ecosystem, and human health - Costa Junior, Ciniro; Escudero, Arthur; Flintan, Fiona; Garrity, Dennis; Gill, Bobby; Haddad, Fidaa; Howell, Daniela; Itzkan, Seth; Louhaichi, Mounir; Magero, Chris; Milne, Eleanor; Neely, Constance; et al. (2022)
The brief is about the case study of two transformative land regeneration approaches developed in Africa: agroforestry and regenerative grazing management. These two approaches come together in silvopastoral systems - livestock grazing and browsing in tree-dotted grasslands - which have been ranked among the most effective carbon drawdown tools at our disposal. This was presented in COP27 in Sharm El-Sheikh, Egypt venue.